2022
DOI: 10.3390/bioengineering9120789
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Mechanical Behavior of Partially Oxidized Polyvinyl Alcohol Hydrogels for Cartilage Tissue Repair

Abstract: Polyvinyl alcohol (PVA) hydrogels are extensively used as scaffolds for tissue engineering, although their biodegradation properties have not been optimized yet. To overcome this limitation, partially oxidized PVA has been developed by means of different oxidizing agents, obtaining scaffolds with improved biodegradability. The oxidation reaction also allows tuning the mechanical properties, which are essential for effective use in vivo. In this work, the compressive mechanical behavior of native and partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The hydrogel showed compressive moduli of 0.33 MPa and 0.12 MPa, respectively, when compressed parallel and perpendicular to the macroporous channels. These moduli are in the same range as native articular cartilage [47][48][49][50][51][52][53][54][55]. Consecutive cyclic (showed hysteresis loop) and stress relaxation (overall stress relaxed around 30%) tests revealed that the Gel-PEG hydrogel was viscoelastic in nature, which made the hydrogel a potential platform for cartilage tissue engineering [38].…”
Section: Stress Relaxation Behavior Of the Anisotropic Gel-peg Hybrid...mentioning
confidence: 80%
See 1 more Smart Citation
“…The hydrogel showed compressive moduli of 0.33 MPa and 0.12 MPa, respectively, when compressed parallel and perpendicular to the macroporous channels. These moduli are in the same range as native articular cartilage [47][48][49][50][51][52][53][54][55]. Consecutive cyclic (showed hysteresis loop) and stress relaxation (overall stress relaxed around 30%) tests revealed that the Gel-PEG hydrogel was viscoelastic in nature, which made the hydrogel a potential platform for cartilage tissue engineering [38].…”
Section: Stress Relaxation Behavior Of the Anisotropic Gel-peg Hybrid...mentioning
confidence: 80%
“…Consecutive cyclic (showed hysteresis loop) and stress relaxation (overall stress relaxed around 30%) tests revealed that the Gel-PEG hydrogel was viscoelastic in nature, which made the hydrogel a potential platform for cartilage tissue engineering [38]. This time-dependent response of the hydrogel is due to the contribution of the viscoelastic behavior of the polymer matrix and water migration through the hydrogel pores [48,56]. The hydrogel showed excellent shape recoverability during the cyclic loading-unloading test.…”
Section: Stress Relaxation Behavior Of the Anisotropic Gel-peg Hybrid...mentioning
confidence: 99%
“…This material represents a sort of evolution from the non-resorbable polyvinyl alcohol, of which the commercially available SaluBridge TM /SaluTunnel TM (Salumedica LLC) guides are made. With respect to its native counterpart, OxPVA is distinguished by a tunable biodegradation rate, highly potential bioactivity, and adjustable physical characteristics, thus standing out as a customizable polymer, as proved by the ability to satisfy different prosthesis characteristics for different tissue targets [36,69,70,102,[106][107][108][109][110][111]. Additionally, the possibility to be "impressed" or poured with/within specific molds and safely physically cross-linked (freezing-thawing method) without potentially toxic chemical agents is also fundamental from the perspective of creating "cell-instructive devices" (such as those encouraging an orderly regeneration of the axons) with no cytotoxic effect [69].…”
Section: Discussionmentioning
confidence: 99%
“…In the wide panorama of biomaterials, the new OxPVA stands out revealing as a promising resource for smart prosthesis fabrication in tissue engineering [ 2 , [16] , [17] , [18] , 20 , 29 , 43 ]. However, despite first appealing in vivo results, its specific chemical and physical characteristics still allow for intense research and development activities [ 22 , 23 , 43 , 44 ] to assure a fine control over pro-regenerative behaviour of the derived devices.…”
Section: Discussionmentioning
confidence: 99%